El navegar del control de convencionalidad bajo la dirección de las sentencias emitidas por la corte interamericana de derechos humanos (2020)
This work refers only to the analysis of the sentences prior to the birth ofConventionality Control and the identification of a series of scattered ideassuch as: violation per se; international responsibility, examination of thewhole, iura novit curia principie, trespassing and duties of the State; which, when combined, result in the concept of conventionality control as a whole. On the other hand, once the concept was integrated into the academic field, the nuances that have been integrated into the voice should be noted, since at the beginning it should be understood that only the Inter-American Court was in charge of the application of the international normative. However, later on the application is extended to any type of judge in Latin America, to end up indicating that the question is the responsibility of any type of authority. Very similar situation occurred with the legal framework that was protected through the conventionality control, as well as the activities that could be done with it, because now the control of conventionality goes beyond the mere disregard of rules by the judges.